New Insight into Selective Serotonin Receptor Agonists in the Central Nervous System, Studied with WAY163909 in Obese and Diabetic Wistar Rats - Ivaylo Bogomilov; Nadka Boyadjieva; Rumen Nikolov (Brain Sciences, 2023)
Background and aims: We investigated the effect of WAY-163909, a novel 5-hydroxytryptamine selective 2C receptor agonist on body weight, blood glucose levels, and insulin resistance in obese and diabetic Wistar rats. Materials and methods: We used twenty male Wistar rats with obesity and obesity-induced diabetes and twenty healthy Wistar rats as a control group. Each of these groups was separated into two subgroups: one with a daily intraperitoneal application of WAY-163909 (1 mg/kg) and one without. During the study, body weight, blood glucose levels, and immunoreactive insulin were tracked. Results: A reduction of 5.5% (p < 0.05) in body weight was registered in the rat group with diabetes and obesity and 2.56% in the control group with a daily application of WAY-163909 (1 mg/kg) at the end of the study. Decreases of 35.4% in blood glucose levels at week four in the diabetic and obese rat group with a daily application of WAY-163909 (1 mg/kg) were registered. A reduction of insulin levels of 4.1% (p < 0.05) in the diabetic and obese rats group using WAY-163909 was also observed. Conclusion: In our study, using WAY-163909 (1 mg/kg) led to a reduction of blood glucose levels, immunoreactive insulin, and body weight.